γ-Tubulin in microtubule nucleation and beyond - Sulimenko, Vadym; Dráberová, Eduarda; Dráber, Pavel (Frontiers in Cell and Developmental Biology, 2022)
Microtubules composed of αβ-tubulin dimers are dynamic cytoskeletal polymers that play key roles in essential cellular processes such as cell division, organelle positioning, intracellular transport, and cell migration. γ-Tubulin is a highly conserved member of the tubulin family that is required for microtubule nucleation. γ-Tubulin, together with its associated proteins, forms the γ-tubulin ring complex (γ-TuRC), which templates microtubules. Here we review recent advances in the structure of γ-TuRC, its activation, and centrosomal recruitment. This provides new mechanistic insights into the molecular mechanism of microtubule nucleation. Accumulating data suggest that γ-tubulin also has other, less well-understood functions. We discuss emerging evidence that γ-tubulin can form oligomers and filaments, has specific nuclear functions, and might be involved in centrosomal cross-talk between microtubules and microfilaments.